The Relationship between The Amount and Frequency of Milk Consumption with The Incidence of Stunting in Semarang City - Ridha, Muna; Al Amien, Tsaniatin Nahla; Mardiana, Mardiana; Hidayat, Arif; Yudistira, Satria (Sport and Nutrition Journal, 2023)
Semarang has reduced the stunting rate by 8,6% in 2021. The district with the highest prevalence in Semarang City is Central Semarang with a stunting rate of 7,25%. Efforts to reduce the prevalence of stunting need to be carried out further to reuduce the stunting prevalence in Semarang. Lack of milk consumption is one of the factors that causes stunting. This study used a case-control design by examining nutritional status height/age (stunting) as the dependent variable, amounts, and frequency of milk consumption as independent variables, as well as mother's knowledge, father's education, mother's education, father's occupation, mother's occupation, family income, history Exclusive breastfeeding, and infectious diseases as confounding variables. The research subjects were 24 mothers of stunted toddlers and 24 mothers of toddlers who were not stunted. Bivariate data analysis was performed using the Chi-Square or Fisher test as an alternative. The bivariate analysis results were selected to be continued in multivariate analysis using the logistic regression test. After controlling for confounding variables, the most dominant variable with the incidence of stunting is milk consumption, with an OR value of 12,5. Toddlers with milk consumption ≤38 g/day will have a 12,5 times higher risk of experiencing stunting.